Immunomodulatory effects of progesterone and selective ligands of membrane progesterone receptors - Polikarpova, Anna; Levina, I. S.; Sigai, N.; Zavarzin, I.; Morozov, I. A.; Rubtsov, P. M.; Guseva, A. A.; Smirnova, Olga V.; Shchelkunova, T. A. (Steroids, 2019)
Progesterone (P4) and its analogues regulate various reproductive processes, such as ovulation, implantation, pregnancy maintenance and delivery. In these processes, an important role is played by the immune cells recruited to the female reproductive organs and tissues, where they are exposed to the action of P4. Progestins regulate cellular processes, acting through nuclear steroid receptors (nSRs), membrane P4 receptors (mPRs), and through the sensors. It remains unclear, what type of receptors is used by P4 and its derivatives to exert their effect on the immune cells and how similar their effects are in different types of these cells. We have previously synthesized new progesterone derivatives, among which two selective mPRs ligands, not interacting with nSRs were identified. The objective of this study was to examine the effects of P4 and new selective mPRs ligands on the expression of pro- and anti-inflammatory cytokines in activated human peripheral blood mononuclear cells (PBMCs), THP-1 monocyte cells, and Jurkat T cells. It was demonstrated that the action of P4 and selective ligands was unidirectional, but in different types of the immune cells, their effects were different, and sometimes even opposite. In PBMCs, exposure to these steroids resulted in the increase of mRNA and secreted protein levels of IL-1β, TNFα, and IL-6 cytokines, as well as in the increase of INFγ mRNA level, decrease of IL-2 mRNA level, increase of TGFβ mRNA level, and decrease of IL-4 mRNA and IL-10 secreted protein levels. In monocytes, similarly to PBMCs, expression of IL-1β and TNFα mRNA was increased, but expression of IL-10 was also increased, and the TGFβ expression statistically significantly remained the same. In Jurkat T cells, expression of IL-2 and TNFα mRNA decreased, while expression of IL-10 increased, and expression of TGFβ did not change. Thus, progestins act on the immune cells through mPRs and have both pro- and anti-inflammatory effects, depending on the phenotypes of these cells. The data obtained are important for understanding the complexity of the immune system regulation by progestins, which depends on the type of the immune cells and individual characteristics of the immune system.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Gene expression; Immune cells; Inflammation; Progesterone; Receptors; Selective ligands